Timber beam seismic design – A numerical simulation (Fracture and Structural Integrity, 2018)
To seismic design of timber beam, effect of near-fault ground motion on timber beam has numerically been investigated, with refer to small displacement theory. The simulated near-fault ground motion is applied on the fixed base of timber frame model. The beam is located in single span of a timber frame. The beam has two different size of 1.8 and 3.3 meter length. The seismic load-displacement seismic load-strain and strain-displacement have been calculated for all models and graphically depicted. The beam is designed with nonlinear analysis method and same mechanical properties for all models have been used, in numerical analysis. The numerical analysis results indicate that, the inertial interaction, energy dissipation and nonlinear deformation of beam in timber frame have direct relationship with frame span. In beam with smaller length, higher seismic loading is caused lower displacement. The displacement is reduced with reduction length of the beam. The inertial interaction, energy dissipation and nonlinear deformation are changed in respect to length of beam. The novelty of this paper is developing cycling graphs by using ABAQUS, for improve design of timber frame, and adequate explanation of seismic behavior of timber beam.
Keywords: Seismic load; Timber beam; Displacement; Nonlinear deformation; Cycling graphs